Identification of the bZIP gene family and regulation of metabolites under salt stress in isatis indigotica - Jiang, Ming; Wang, Zhen; Ren, Weichao; Yan, Song; Xing, Nannan; Zhang, Zhanping; Li, Hui; Ma, Wei (Frontiers in Plant Science, 2022)
Isatis indigotica is a cruciferous herb of medicinal and industrial importance. The bZIP transcription factor family plays important roles in plant growth and development, response to stress, and regulation of secondary metabolite biosynthesis, but has not been studied previously in I. indigotica. In this study, 65 IibZIP genes were identified in the genome of I. indigotica and the gene structure, chromosomal location, and phylogenetic relationships were analyzed. The IibZIP genes were distributed on seven chromosomes, were highly conserved, and were classified into 11 subgroups. The promoter region of the IibZIP genes included cis-elements responsive to various abiotic stresses and hormones, and that bind to DNA to interact with other transcription factors to regulate plant responses to abiotic stresses and to regulate secondary metabolite synthesis. Transcriptomic and metabolomic data for leaves of I. indigotica exposed to salt stress were analyzed to construct an IibZIP gene co-expression network and metabolite correlation network. Seventeen IibZIP genes were co-expressed with 79 transcription factors, and GO and KEGG enrichment analysis showed that most of these genes were associated with abiotic stress and hormone responses of plants. In addition, 17 IibZIP genes regulated 110 metabolites through 92 transcription factor associations. Seven differentially expressed IibZIP genes positively regulated 32 differential metabolites. The associated metabolites included a large number of alkaloids, flavonoids, and primary metabolites. This study provides data for identification of the IibZIP gene family and their regulation of metabolites in response to salt stress.